Assessing universal maternal health service coverage and their determinants in India: A multicentric cross-sectional study - Shantanu Sharma; Aditya Bhardwaj; Kanishtha Arora; Faiyaz Akhtar; Sunil Mehra (Journal of Family Medicine and Primary Care)
Introduction: Universal maternal health coverage (UHC) envisages access to quality healthcare services by pregnant and lactating women without any financial hardship. Our present study attempts to assess the UHC for maternal health services and their determinants, including access to quality antenatal care (ANC), quality postnatal care (PNC), and child immunization among the marginalized populations of India. Methods: It was a community-based cross-sectional study across five states of India among pregnant or lactating women. Quality ANC score was calculated using four indicators, including ANC registration month, attendance of four or more ANC visits, receiving at least one tetanus toxoid injection, and consumption of 100 iron-folic acid (IFA) tablets. Similarly, quality PNC care score was calculated using four indicators, including PNC within 48 h, breastfeeding initiation time, institutional delivery, and accessing conditional maternity benefit scheme. Logistic or generalized linear regression was used to depict associations depending on the outcome variables. Results: A total of 12,976 pregnant women’s and 18,061 lactating mothers’ data were analyzed. Illiterate women, women from below the poverty line, and rural areas had low-quality ANC and PNC scores compared with their counterparts. Marginalized women had lower odds of immunization of children and lower quality PNC scores than nonmarginalized. Conclusions: Sociodemographic factors, such as caste, education of women, area of residence, and economic status, are major determinants of quality ANC and PNC scores and immunization of children. Hence, interventionists ought to design community-based interventions that address the challenges in the uptake of health services.